Preparation and Characterization of New Liposomes. Bactericidal Activity of Cefepime Encapsulated into Cationic Liposomes - Maria Luisa Moyá; Manuel López-López; José Antonio Lebrón; Francisco José Ostos; David Pérez; Vanesa Camacho; Irene Beck; Vicente Merino-Bohórquez; Manuel Camean; Nuria Madinabeitia; Pilar López-Cornejo (MDPI AG, 2019)
Cefepime is an antibiotic with a broad spectrum of antimicrobial activity. However, this antibiotic has several side effects and a high degradation rate. For this reason, the preparation and characterization of new liposomes that are able to encapsulate this antibiotic seem to be an important research line in the pharmaceutical industry. Anionic and cationic liposomes were prepared and characterized. All cationic structures contained the same cationic surfactant, N,N,N-triethyl-N-(12-naphthoxydodecyl)ammonium. Results showed a better encapsulation-efficiency percentage (EE%) of cefepime in liposomes with phosphatidylcholine and cholesterol than with 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE). The presence of cholesterol and the quantity of egg-yolk phospholipid in the liposome increased the encapsulation percentage. The bactericidal activity against Escherichia coli of cefepime loaded into liposomes with phosphatidylcholine was measured. The inhibitory zone in an agar plate for free cefepime was similar to that obtained for loaded cefepime. The growth-rate constant of E. coli culture was also measured in working conditions. The liposome without any antibiotic exerted no influence in such a rate constant. All obtained results suggest that PC:CH:12NBr liposomes are biocompatible nanocarriers of cefepime that can be used in bacterial infections against Escherichia coli with high inhibitory activity.